ANALISIS KEBUTUHAN E-MODUL BERBASIS MASALAH MENGGUNAKAN APLIKASI MOODLE MATERI KIMIA SISWA SMA/MA KELAS XI SEMESTER II - Siti Khodijah Dalimunthe; Nurfajriani Nurfajriani; Murniaty Simorangkir (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
This study aims to analyze the need develop a teaching material needed in schools, namely problem-based e-module using Moodle on chemistry material for even semester XI SMA. This type of research is part of development research using ADDIE. This research is only up to in the first stage. Subject and location of this research are chemistry teachers and students of class XI SMA N 1 Binjai Langkat district. research instrument used interview questionnaires and BSNP assessments. the research obtained several result, namely schools using the 2013 curriculum, teaching materials in the form of textbooks. The existence of textbooks is still abstract and the level is too high so it is difficult for students to understand. The problem-based learning model and use of electronic media in learning hav'nt implemented. The chemistry textbook analyzed was concluded to be suitable for use, however, in the book, the material contained is very short, does'nt contain multimedia links as additional reference material that can enrich students' insight and make it easier to understand the material. can be concluded that it is necessary to develop problem-based e-module teaching materials using the Moodle application on chemistry material for even semester XI SMA. Keywords: Needs Analysis, E-Module Media